2015
DOI: 10.1088/0268-1242/30/10/105008
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Si–Ge interdiffusion in high phosphorus-doped germanium on silicon

Abstract: Si-Ge interdiffusion with different P doping configurations was investigated. Significant interdiffusion happened when the Ge layers were doped with P in high 10 18 cm −3 range, which resulted in a SiGe alloy region thicker than 150 nm after defect annealing cycles. With high P doped Ge, Si-Ge interdiffusivity is enhanced by 10-20 times in the x Ge > 0.7 region compared with the control sample without P doping. We attribute this phenomenon to the much faster P transport towards the Ge seeding layers from the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Our recent study showed that high P doping greatly accelerates Si-Ge interdiffusion due to the Fermi-level effect [18]. Si-Ge interdiffusion can change a Ge layer into a SiGe alloy, which delays the lasing of Ge lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study showed that high P doping greatly accelerates Si-Ge interdiffusion due to the Fermi-level effect [18]. Si-Ge interdiffusion can change a Ge layer into a SiGe alloy, which delays the lasing of Ge lasers.…”
Section: Introductionmentioning
confidence: 99%
“…The interdiffusion regions for undoped Ge/Si (UGUS) and P-doped Ge/Si (PGPS) are about 60 and 225 nm thick if we define the interdiffusion region is where 0.02 < xGe < 0.98. If we define the interdiffusion region is where 0.05 < xGe < 0.95, the alloy regions are about 45 and 159 nm thick for UGUS and PGPS respectively, which are significant portions of the Ge films, commonly a few hundred of nanometers, for Ge-on-Si lasers [2]. Fig.…”
Section: Concepts and Examplesmentioning
confidence: 99%
“…shift on emission (band gap narrowing) shows the differences on dopant concentration between the different samples. Given that there is a linear dependence between the Γ-point bandgap shrinkage and heavy n-doping [29], the band narrowing can be predicted using the dopant concentration given on Table 1 for each of the samples. Using a first order phenomenological model for band gap narrowing and using the values of = 0.013 and Δ = 10 −21 / −3 given for Ge [41], the narrowing was calculated and is summarized on Table 4 below.…”
Section: Ge and Dopant Concentrationmentioning
confidence: 99%
“…The high thermal budget associated with these steps is not desired, as it drives Si-Ge interdiffusion as well as dopant out-diffusion [27], and thus counteracts the efforts in bandgap engineering. Especially, interdiffusion is enhanced with n-type doping by a factor of 2 to 6 with P doping and 1.5 to 3 times with As doping in low to mid-10 19 cm -3 range [28][29][30].…”
mentioning
confidence: 99%